COMPARATIVE ANATOMICAL STUDIES ABOUT CHICKEN SUB-BASAL CONNECTIONS - CARMEN BERGHES; MONICA PARVU; D. CUCA; M. CUCANES (Scientific Papers Animal Science and Biotechnologies, 2023)
The studies aimed to describe the nervous formations from the base of the cranium in the hen and domestic duck. These clarifications are necessary in order to disclose some unknown facts regarding this region in the poultry species used preponderantly in laboratory studies of the aviary flu. The vegetative connections from the base of the skull have been studied on 10 poultry specimens, 5 hens and 5 ducks. The animals have been euthanatized using chloroform and a special dye has been injected through the heart in order to achieve a better differentiation of the nervous formations. Dissection was performed under a magnifying glass using instruments adequate to highly fine dissections. Photos and sketches of the dissected pieces have been taken. Nomina Anatomica (2003) was used to describe the observed formations.The studies showed that the cranial cervical ganglia around which is the sub-basal nervous tissue, is located on the border of the occipital hole, at the basis of the temporal pyramid, much deeper than in mammalians; it is better developed in the duck (3-4 mm) than in the hen (1-2 mm); the cranial cervical ganglia has the shape of a globe in gallinaceans and it is long in shape in the ducks. A multitude of connecting branches were observed around the lymph node, linking it to the vague nerve, to the hypoglossal nerve, to the glossopharyngeal nerve and to the transversal paravertebral chain which is specific to poultry; an obvious branch detaches from the cranial pole, which is the sub-basal connective, while the cervical connective detaches from the caudal pole, connecting it to the cervical-thoracic lymph node.